1996
DOI: 10.1016/s0009-9236(96)90021-1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of vinorelbine in patients with liver metastases

Abstract: These results support vinorelbine dose reduction in patients with severe liver failure but not in patients with moderate secondary liver involvement. The monoethylglycinexylidide test may prove to be useful for vinorelbine dose individualization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 22 publications
2
31
1
Order By: Relevance
“…Alteration in liver function related to either hepatic insufficiency or presence of liver metastases should impact the elimination of vinorelbine. No effect of liver metastases on vinorelbine clearance was found, which is in accordance with the finding of Robieux et al [21] with IV vinorelbine. They demonstrated that only a major invasion (more than 75%) of the liver by metastases can decrease the vinorelbine clearance.…”
Section: Discussionsupporting
confidence: 92%
“…Alteration in liver function related to either hepatic insufficiency or presence of liver metastases should impact the elimination of vinorelbine. No effect of liver metastases on vinorelbine clearance was found, which is in accordance with the finding of Robieux et al [21] with IV vinorelbine. They demonstrated that only a major invasion (more than 75%) of the liver by metastases can decrease the vinorelbine clearance.…”
Section: Discussionsupporting
confidence: 92%
“…Although long-term survival can be achieved in some patients with limited hepatic disease [4], the prognosis for patients with disseminated liver metastases is commonly poor, and a median survival of 14 months after initial diagnosis of liver metastases can be expected [5,6]. Advanced liver metastases can cause hepatic dysfunction which is clinically apparent by hepatomegaly, jaundice, or the formation of ascites due to cholestasis and/or portal hypertension [7][8][9]. In general, liver metastases from breast cancer respond to chemotherapy [10], and anthracyclines and taxanes are still the most effective drugs for first-line treatment [11][12].…”
Section: Introductionmentioning
confidence: 99%
“…However, the efficacy of chemotherapy is frequently suboptimal as compared to other metastatic sites, as drug activity can be affected by impaired metabolic liver function [1]. Furthermore, hepatic dysfunction often limits the therapeutic options in these patients due to insufficient biliary drug clearing [8,9], and severe toxicity has been reported after administering standard dose regimens [13][14][15]. In particular, persisting hyperbilirubinemia with serum levels > 2 mg/dl precludes the use of most cytotoxic drugs [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Although a weak correlation exists between serum bilirubin level and vinorelbine clearance, current adjustments for this agent are based on serum bilirubin [29].…”
Section: Vinorelbinementioning
confidence: 99%